PERMIAN STRATIGRAPHY AND FUSULINIDS OF THE TETHYS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
The diversity curve of Permian fusulinid genera shows two peaks corresponding to the Asselian-Sakmarian and Midian times. The minimal generic diversity is recorded in the late Bolorian. The most significant extinction events occurred at the end of the Midian (71% of all genera), Bolorian (48%), Asselian (27%) and Sakmarian (23%) ages. The fusulinid assemblage was most notably changed by the appearance of new genera (52% of the total number) in the Kubergandian age. These data  identify two main stages (Asselian-Bolorian and Kubergandian-Dorashamian) and four second-order stages (Asselian-Sakmarian, Yakhtashian-Bolorian, Kubergandian-Midian, and Dzhulfian-Dorashamian) in the Permian history of fusulinids. The main stages correspond to two Permian series of the East European scale, which can be considered as subsystems named Cisuralian and Tethysian, respectively. The latter are subdivided into the Uralian, Darvasian, Yanghsingian and Lopingian series which correspond to the second-order stages. The scale suggested does not contradict the traditional two-member subdivision and has an advantage over the accepted global three-member chronostratigraphic scale because the series suggested are more proportional to each other in scope and reflect natural evolutionary processes of the marine biota. In addition, the application of the global scale to the Tethyan sequences is hampered by a limited number of criteria used in the drawing of series and stage boundaries, as evidenced by the existing different views on the position of the lower Guadalupian boundary in the Tethyan sections.